Improving the supply chain of motor pumps to expand small-scale private irrigation in Zambia - Colenbrander, W.; van Koppen, Barbara (International Water Management Institute, 2012)
During the past decade, smallholder groundwater irrigation with motor pumps has increased considerably in Zambia. The present study analyzes an important, but hitherto ignored, factor for adoption: the supply chain of imported motor pumps. Findings include types of pumps; organization of import, wholesale and retail, including after-sales services; fiscal measures (import duty waiver and VAT zero rating); prices of pumps; and financing facilities to the farmers. The main obstacles for farmers were found to be: the highly centralized supply chain and financing facilities in urban hubs; lack of information, also about prices, which vary significantly even for the same make and model of pump; lack of information and training about proper use and maintenance; and lack of financing facilities. The Zambia National Farmers Union seems best placed to remove these obstacles.